Study of the inhibitory effect of the ethanolic extract of a number of local medicinal plants on the growth of proteus spp. in vitro: Jinan Abdul-Amir Sabeeh@ and Zainab Adnan Hatem - Sabeeh, Jinan Abdul-Amir (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was designed to evaluate the inhibitory effect of six local medicinal plants ethanolic extract ( Quercusrobur, Vitisvinifera, Cinamomumzeylanicum , Ginger officinale ,Thymus vulgaris and Coriandrumsativum ) on the growth of Proteus spp. in vitro. For this purpose graduate concentrates for each extract (50, 100, 200 and 400) mg/ml were prepared and tested. The result showed that all the studied medicinal plants have antibacterial activity against Proteus spp. with exception for Coriandrumsativum which didn’t showed any inhibitory activity for the growing of the studied bacteria in Vitro. And the more active plant in inhibition the growth of the studied bacteria was Quercusrobur followed by Vitisvinifera and Cinamomum zeylanicum , Ginger officinale ,Thymus vulgaris. Also, there was no significant differences between the effect of the different concentrations of Thymus vulgaris and Coriandrum sativum, while there were a significant differences between effect of Cinamomumzeylanicum concentrations and the concentrations of (400 and 200 mg\ml) Ginger officinale and compared with 100 and 50 mg/ml of Quercusrobur, while, the ethanolic extract of the Vitisvinifera showed a significant differences between the effect of the concentration 400 mg\ml with the other studied concentration.